Buckling of the initial imperfect rectangular thin plate with variable thickness - Luong, Nguyen Thi Hien; Tuong, Dang Thuy Minh (Vietnam Journal of Mechanics, 2006)
This paper analyzes the stability of the rectangular thin plate with sinusoidal changes in the plate thickness combined with initial curvature based on the large deflection theory. The buckling load for simply supported plates is defined using the energy method. The influence of the thickness variation parameter and the initial curvature parameter on the critical loads is investigated